1999
DOI: 10.1104/pp.120.1.293
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Lipid Integrity Relies on a Threshold of ATP Production Rate in Potato Cell Cultures Submitted to Anoxia1

Abstract: In this paper we report on our study of the changes in biomass, lipid composition, and fermentation end products, as well as in the ATP level and synthesis rate in cultivated potato (Solanum tuberosum) cells submitted to anoxia stress. During the first phase of about 12 h, cells coped with the reduced energy supply brought about by fermentation and their membrane lipids remained intact. The second phase (12-24 h), during which the energy supply dropped down to 1% to 2% of its maximal theoretical normoxic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(79 citation statements)
references
References 33 publications
5
74
0
Order By: Relevance
“…Eight hours after induction, we divided the culture in halves. To deplete the level of ATP, we treated half with the ATP synthesis inhibitor cocktail (NaF, a glycolysis inhibitor, as well as NaN 3 , and carbonylcyamide m-chlorophenylhydrazone, mitochondrial electron chain and phosphorylation inhibitors) used by Rawyler et al (1999) and found that the cell-associated radioactivity increased rapidly ( Figure 6C), indicating that sclareolide extrusion is linked to an energetic process.…”
Section: Efflux Of the 3 H-sclareolide Derivative Correlates With Npamentioning
confidence: 99%
See 1 more Smart Citation
“…Eight hours after induction, we divided the culture in halves. To deplete the level of ATP, we treated half with the ATP synthesis inhibitor cocktail (NaF, a glycolysis inhibitor, as well as NaN 3 , and carbonylcyamide m-chlorophenylhydrazone, mitochondrial electron chain and phosphorylation inhibitors) used by Rawyler et al (1999) and found that the cell-associated radioactivity increased rapidly ( Figure 6C), indicating that sclareolide extrusion is linked to an energetic process.…”
Section: Efflux Of the 3 H-sclareolide Derivative Correlates With Npamentioning
confidence: 99%
“…Eight hours after induction, we divided the culture in halves. To deplete the level of ATP, we treated half with the ATP synthesis inhibitor cocktail (NaF, a glycolysis inhibitor, as well as NaN 3 , and carbonylcyamide m-chlorophenylhydrazone, mitochondrial electron chain and phosphorylation inhibitors) used by Rawyler et al (1999) and found that the cell-associated radioactivity increased rapidly ( Figure 6C), indicating that sclareolide extrusion is linked to an energetic process.Using another approach, we compared the labeled sclareolide derivative associated with control cells and cells that had been incubated for 12 hr with unlabeled sclareolide. The terpenoid-pretreated cells showed less accumulation than the untreated cells, and this difference was removed by ATP synthesis inhibitors ( Figure 6D).…”
mentioning
confidence: 99%
“…In practice this means that cells can survive for a certain period before metabolism is seriously hampered. For example, potato cells in culture showed no membrane damage for the first 12 h after imposition of anaerobic stress (Rawyler et al, 1999). Thereafter, free fatty acids accumulated in the potato cells coincident with the calculated energy supply decreasing to 1-2% of the aerobic maximum.…”
Section: Anaerobic Stress and Flooding Tolerance Of Plantsmentioning
confidence: 99%
“…From this, and studies with inhibitors, it was suggested that there is a threshold of ATP production of approx. 10 µmol g −" f. wt h −" , below which membrane structure cannot be preserved (Rawyler et al, 1999). The restricted ATP supply also has direct implications for proteolysis.…”
Section: Anaerobic Stress and Flooding Tolerance Of Plantsmentioning
confidence: 99%
See 1 more Smart Citation